1c(w−2vv+w)
1c(w−2vv−w)
1c(w+2vv−w)
1c(w+2vv+w)
Correct answer is A
w = v(2+cn)1−cn
2v + cnv = w(1 - cn)
2v + cnv = w - cnw
2v - w = -cnv - cnw
Multiply through by negative sign
-2v + w = cnv + cnw
-2v + w = n(cv + cw)
n = −2v+wcv+cw
n = 1c−2v+wv+w
Re-arrange...
n = 1cw−2vv+w
In triangles XYZ and XQP, XP = 4cm, XQ = 5cm and PQ = QY = 3cm. Find ZY ...
A fair coin is tossed three times. Find the probability of getting two heads and one tail. ...
Find the equation whose roots are 2 and −312...
If y = x2 - 2x - 3, Find the least value of y and corresponding value of x...
From a point P, Q is 5km due West and R is12km due South of Q. Find the distance between P...
Factorize r2 - r(2p + q) + 2pq ...